The rhyme in Marina Tsvetaeva’s ''Poetry of the word'' (with the poem Nebo – sinei znameni! “The sky is bluer than the flag!” as an example) - Roberta Salvatore (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
The aim of this paper is to present one of the main mechanisms of semantic creation in Marina Tsvetaeva’s poetry through the analysis of the poem Небо — синей знамени! (“The Sky is Bluer than the Flag!”, 1935). This text demonstrates the opposition between time and eternity by means of adjoining fi ve nouns which are united by a rather rare infl ectional pattern (neuter nouns with the nominative singular in -мя) in rhyming position. The choice of this particular range of vocabulary serves as evidence to the poet’s desire to test the semantic potential of words similar in their declension type rather than in their meaning. In her construction of the text, the language rather than the world is primary, and it is the language that reality is being checked against. The specifi city of this feature to Tsvetaeva’s creative work is proved by examining its realisation in other texts, namely in the poem Променявши на стремя by Tsvetaeva herself and in Akhmatova’s text from the 1960s Из набросков. In the fi rst text, this specifi c rhyming does not cover the whole text, and the theme expressed by its associative range is still one-dimensional. Akhmatova’s poem clearly demonstrates that this technique can be employed in various ways for poetic purposes. The analysis of the text allows us to conclude that the prominence of this technique depends primarily on the role that it plays in expressing the poetic thought, whereas the number of same-type words in the rhyming position is a secondary factor.